Production Planning in PT. Rekayasa Agri Utama - Fauzia, Zerlinda Nur; Handayati, Yuanita (Journal of Business and Management, 2019)
Background: One of the important stages before starting production activities is production planning. The company have to calculated the product completion time. The delay in production will reduce customer trust because the company can not fulfill the customer demand. While, if the production completed early, it will increasing holding cost. To making the appropriate production planning, an accurate forecast is needed in order to prevent excess and insufficient amount of production then make the appropriate production planning through master production schedule. PT.Rekayasa Agri Utama(RAU) is a company engaged in the agribusiness industry, which was established to produce and distribute probiotic microbes with the SIMBA trademark. Currently, PT. RAU is facing inventory buildup because they did not yet have a good production scheduling system and demand forecasting system. So the purpose of this study is to determine the appropriate demand forecasting system in Degra Simba products at PT. RAU and determine the quantity of production, and quantity of safety stock.Methods: To determine the forecasting system that is in accordance with PT.RAU, this study uses a demand forecasting method which is included in the Time Series Analysis category. Each demand forecasting method is compared with the actual demand, so the method that is most suitable for PT.RAU is a method that has the smallest error value. After determining the most suitable forecasting method, then to overcome the problem of inventory accumulation this research also makes aggregate planning for company used the strategy which has the lowest cost for company.Results: The results of the study show that the forecasting method that is most suitable with PT.RAU is the Moving Average method because the method has the smallest error. By using this model, it indicates that data demand on Degra Simba has no trends or seasonal. Inventory buildup that occurs in the company can be overcome by making an aggregate planning using the aggregate planning strategy which has the lowest cost that is linear programming strategy. By applying linear programming strategy PT. RAU can save Rp230,709,900.Conclusion: PT.RAU should apply the moving average method as a demand forecasting system and Linear Programming Strategy as their production planning.Keywords: forecasting demand, production planning, aggregate planning, linear programming strategy, degra simba.